UNDERSTANDING THE MEANING OF RACIAL-BASED BULLYING MESSAGES OF BIRACIAL ADOLESCENT - Salsabila Putri Wasesa, Meidyana; Rahardjo, Turnomo (Interaksi Online, 2024)
This research aims to explore the meaning behind racially-based bullying messages experienced by biracial adolescents. Racial bullying targets the physical features or ethnic identity of the victim, often resulting in significant effects on their personal development and mental well-being. Using the Interpretative Phenomenological Analysis (IPA) approach, this study delves into the lived experiences of several biracial adolescents aged 12-19, with mixed heritages including Indonesia-Korea, Indonesia-India, Indonesia-New Zealand/Dutch, and Indonesia-Nigeria. In-depth interviews served as the primary method of data collection, focusing on the victims' interpretations of the bullying messages they encountered. Symbolic Interactionism Theory and Coordinated Management of Meaning (CMM) were applied to analyze how victims make sense of and respond to these racially motivated messages within their social relationships. The findings suggest that biracial adolescent as victims interpret the racial-based messages as deeply ingrained with racial stereotypes. Additionally, the findings also revealed that biracial adolescent understand the act of racial-based bullying as act of social exclusion and the construction of self-doubt. These racial-based messages interpretation leads to a negative self-concept and the development of trust issues. Moreover, biracial adolescent interpreted the process of communication with family, friends, and school authorities as the efforts to seek support and process their emotions. In conclusion, the findings indicate that biracial adolescents perceive racial-based bullying messages as deeply rooted in racial stereotypes and view these acts as forms of social exclusion that foster self-doubt. Racial-based bullying not only affects the psychological development of biracial adolescents but also shapes their understanding of their racial identity. This study highlights how biracial adolescent make sense of the experience they faced in order to form coping mechanism.